(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
In more than two decades of nature tourism development in Mexico mainly by indigenous companies, these organizations emerge and disappear without you have obtained a characterization of them. Hence the importance of this document, the product of an exploratory and descriptive research, which provides an overview of indigenous nature tourism companies from a number of categories like, your offer, origin, organization, certifications, among others. The methodology used was documentary analysis and processing of electronic and printed information sources designed ad hoc basis. Among the main findings highlight that these businesses are concentrated in multicultural and biodiverse regions; profit social organizations are responding to the market, the interest of the community and sustainability initiatives. Mostly are products of sectoral government interventions to combat poverty and environmental conservation. They are subject to traditional customs and practices that although amalgamate, can also mean obstacles in their business development. However, its main strength is its capital that has value to tourism for its natural and cultural heritage. Although offered all forms of nature tourism, they have developed mainly ecotourism. They are complementary to traditional economic activities of communities but which can contribute to improving the quality of life of its members from the recognition of their own natural, cultural and social wealth and empowerment of the social group productive options. .